A comparative ultrastructural analysis of spermatozoa in Pleurodema (Anura, Leptodactylidae, Leiuperinae). (6th May 2016) - Cruz, Julio C.; Ferraro, Daiana P.; Farías, Alejandro; Santos, Julio S.; Recco‐Pimentel, Shirlei M.; Faivovich, Julián; Hermida, Gladys N.
ABSTRACT: This study describes the spermatozoa of 10 of the 15 species of the Neotropical frog genus Pleurodema through transmission electron microscopy. The diversity of oviposition modes coupled with a recent phylogenetic hypothesis of Pleurodema makes it an interesting group for the study of ultrastructural sperm evolution in relation to fertilization environment and egg‐clutch structure. We found that Pleurodema has an unusual variability in sperm morphology. The more variable structures were the acrosomal complex, the midpiece, and the tail. The acrosomal complex has all the structures commonly reported in hyloid frogs but with different degree of development of the subacrosomal cone. Regarding the midpiece, the variability is given by the presence or absence of the mitochondrial collar. Finally, the tail is the most variable structure, ranging from single (only axoneme) to more complex (presence of paraxonemal rod, cytoplasmic sheath, and undulating membrane), with the absence of the typical axial fiber present in hyloid frogs, also shared with some other genera of Leiuperinae. J. Morphol. 277:957–977, 2016. © 2016 Wiley Periodicals, Inc.